Platone e il governo misto - Giuseppe Cambiano (Montesquieu.it, 2011)
This paper discusses Plato’s political philosophy in the light of Polybius’s theory of mixed government or regimen mixtum. The article focuses mainly on Plato’s Statesman and Laws